2012
DOI: 10.1007/s00216-012-5856-3
|View full text |Cite
|
Sign up to set email alerts
|

Time course of expiratory propofol after bolus injection as measured by ion molecule reaction mass spectrometry

Abstract: Propofol in exhaled breath can be detected and monitored in real time by ion molecule reaction mass spectrometry (IMR-MS). In addition, propofol concentration in exhaled breath is tightly correlated with propofol concentration in plasma. Therefore, real-time monitoring of expiratory propofol could be useful for titrating intravenous anesthesia, but only if concentration changes in plasma can be determined in exhaled breath without significant delay. To evaluate the utility of IMR-MS during non-steady-state con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Several investigators have measured the propofol efficacy by BIS and in exhaled air . For example, Buchinger et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have measured the propofol efficacy by BIS and in exhaled air . For example, Buchinger et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Hornuss et al . ). In IMR‐MS, positively charged atomic ions interact with neutral sample gas molecules.…”
Section: Methodsmentioning
confidence: 97%
“…In the first study, comparisons between blood propofol, and propofol in the exhaled breath of patients undergoing intravenous anesthesia were monitored and the conclusion was reached that IMR-MS may allow continuous noninvasive monitoring of propofol levels in patients undergoing general anesthesia [40]. A second study also on propofol found that IMR-MS can detect propofol on human breath within seconds after a bolus injection [44]. Another investigation using IMR-MS examined breath gas from patients who were mechanically ventilated and compared the results from IMR-MS with a conventional electron impact mass spectrometer for monitoring CO 2 .…”
Section: Medicalmentioning
confidence: 98%